Decolourisation of a synthetic textile effluent using a bacterial consortium - Ramalho, Patrícia A. (2007)
In the present study we examined the performance of a thermoalkalophilic bacterial consortium, where the predominant strain was Bacillus sp. SF, in the degradation of Reactive Black 5 (RB5). We used a reactor working in continuous mode and investigated the effects of pH, hydraulic retention time (HRT) and several added salts on colour and chemical oxygen demand (COD) reductions. For the chosen operational conditions (pH 9, 55ºC and HRT of 12 h) the efficiencies achieved were 91.2 ± 0.8 % for colour removal and 81.2% for COD removal. The system tolerated, with no significant decrease in colour removal efficiency, 30 g/L Na2SO4, Na2CO3 or NaCl. The latter two salts, however, led to a reduction in COD removal of 30% and 50%, respectively. The system proved to be very effective in the decolourisation of C.I. RB5 under alkaline conditions and at a comparatively high temperature.